Die germanische Mythosgestalt *Askiz in der Germania von Cornelius Tacitus und in altnordischen Quellen - Krzysztof Tomasz Witczak; Elwira Kaczyńska (Brünner Beiträge zur Germanistik und Nordistik, 2016)
The work by Publius Cornelius Tacitus entitled De origine et situ Germanorum is an inexhaustible source of knowledge about ancient Germanic peoples, their culture, beliefs and even their mythology. The proposed paper compares Tacitus' information on the actions of Germanic *Askiz, identified with Greek-Roman Ulysses (Germ. 3, 2–3) and the Germanic myth of the creation of man (Germ. 2,2) with corresponding mentions from the Old Norse tradition (Völuspa, stanzas 17–18; Snorri Sturluson, Edda. Gylfaginning). The authors conclude that interpreting the stanzas 17–18 of the Old Norse Voluspa as a myth of the creation of man (widely accepted so far and supported by the authority of the 13th century Icelandic writer Snorri Sturluson) is groundless. The Old Norse text mentions only an accidental interference of three Gods: Odin, Hoenir and Lodur in the life of particular human beings. The Gods, strolling by the seashore find Ask and Embla lying unconscious and they bring them to life, giving them spirit, sense, blood and skin colour. The passage is most probably a description of one of the adventures of the mythical Germanic wanderer *Askiz, the founder of the town of Asciburgium on the left bank of the Rhine (today Moers-Asberg, near Düsseldorf), according to Tacitus' informants. The original Germanic myth of the creation of mankind is described in Tacitus' work. The report of it is fully credible because it contains both elements directly attributable to the Indo-European tradition (Germanic Mannus as Indo-European *MonHus, the forefather of all mankind) as well as elements related to Proto-Germanic origins e.g. the eponymous ancestors of Ingvaeones and Herminones, whose existence is corroborated by later mythological data (e.g. Gmc. *Ingwaz / *Ingwōn, whence OE. Ing, ON. Ingwi; Gmc. *Ermenaz, whence OSax. Irmin).